Validation of Malay version of five-factor nonverbal personality questionnaire (FF-NPQ) - Rashid, Nurul Fitriah Ab (2016)
Introduction: The Five-Factor Nonverbal Personality Questionnaire (FF-NPQ) is a questionnaire measuring five broad dimension of Big Five theory of personality. It consists of 60 items with five constructs, 12 items each. This questionnaire is different from other personality questionnaire since each item is expressed in form of illustration of a situation. Although this inventory has some advantages as compared to other personality inventory, there is no study carried out to validate the questionnaire to suit it with Malaysian culture and environment. Objective: The study was conducted to validate the Malay version of FF-NPQ among Malaysians young adults. Methods: The study was a cross-sectional study conducted in Health Campus, USM among the young adults aged 18 to 30 years old. Respondents were selected among undergraduate and postgraduate students of 2015/2016 academic session. Number of the sample was 153 respondents. Translation process was done by forward and backward translation method. Confirmatory factor analysis (CFA) was applied to find the construct validity based on internal structure evidence by dimensionality. Independent t-test was applied to find the construct validity based on relationship with other variables while Mann- Whitney test was applied when assumptions of independent t-test were violated. Results: At the end of this study, the Malay version of FF-NPQ was produced. The CFA resulted in good model fit (FF-NPQ revised) with five factors were maintained and 26 items remained (χ2(df), p-value = 315.53 (286), 0.111; CFI = 0.958; TLI = 0.952; RMSEA (90% CI) = 0.026 (0.000, 0.042); SRMR = 0.068; AIC = 13824.13; BIC = 14099.30). Three correlated errors were also considered in the final model. Each construct also have a good reliability range from 0.68 to 0.77. Independent t-test andMann-Whitney test resulted in four variables were significant (p-value < 0.05). Conclusion: The Malay version of FF-NPQ has a potentially good construct validity and reliability in the scope of this study. The questionnaire maintained the broad five factor personality dimension as its five factors at the end of the study, namely Extraversion, Agreeableness, Conscientiousness, Neuroticism and Openness to experience.